Swertiamarin ameliorates diet-induced obesity by promoting adipose tissue browning and oxidative metabolism in preexisting obese mice - Zhu Yuqin; Li Haoran; Ma Mengchen; Li Dandan; Zhang Ouyang; Cai Suili; Wang Yajiao; Chen Dandan; Jin Shengnan; Ding Chunming; Xu Liang (Acta Biochimica et Biophysica Sinica, 2022)
Obesity is a risk factor for many metabolic diseases. Efficient therapeutic strategies are urgently needed. Swertiamarin (STM) prevents obesity and the associated insulin resistance and inflammation. However, the therapeutic effects of STM on preexisting obesity remain unclear. Therefore, in this study we aim to investigate the effects of STM on energy expenditure and fat browning in mice with preexisting obesity. C57BL/6J mice are fed with a high-fat diet (HFD) for 8 weeks to induce obesity and then gavaged (or not) with STM for 10 weeks. The whole-body energy metabolism of mice is examined by indirect calorimetry. The results show that after 10 weeks of treatment, STM markedly prevents HFD-induced weight gain, chronic inflammation, insulin resistance, and hepatic steatosis. STM promotes oxygen consumption and energy expenditure. The level of uncoupling protein 1 is enhanced in the brown and white adipose tissues of STM-treated mice. STM increases the phosphorylation of AMP-activated protein kinase and the expressions of genes involved in fat oxidation, reducing fat deposition in skeletal muscles. Meanwhile, STM does not affect the intestinal microbiotic composition. Overall, STM supplementation may serve as a potential therapy for obesity.